Islamic Religious Education Lesson Learning Design Using the ADDIE Model: Conceptual Framework and Practice in Elementary Schools (Desain Pembelajaran Pelajaran Pendidikan Agama Islam dengan Menggunakan Model ADDIE: Kerangka Konseptual dan Praktik di Sekolah Dasar) - Abbas, Abbas; Hukrandi, Hukrandi (Shautut Tarbiyah-IAIN Kendari, 2024)
This article discusses the learning design for Islamic Religious Education (PAI) subjects in Elementary Schools using the ADDIE model as a conceptual framework. The ADDIE model, which consists of five stages—Analysis, Design, Development, Implementation, and Evaluation—offers a systematic and comprehensive approach to designing effective and relevant learning to students' needs. This study uses a qualitative approach by conducting a literature study, namely reviewing various literature related to the ADDIE learning model and PAI learning in Elementary Schools. The results of the study indicate that the application of the ADDIE model in PAI learning design can improve the effectiveness of teaching in a more structured, adaptive, and in accordance with curriculum objectives. This article also identifies challenges and best practices in implementing the ADDIE model in Elementary School environments, providing recommendations for educators to improve the quality of PAI learning. Thus, the ADDIE model has proven to be an effective tool in developing learning strategies that can shape students' character and spirituality optimally. Keywords:     Learning Design, Islamic Religious Education, ADDIE Model, Elementary School, Conceptual Framework